Epigenetic mechanisms in multiple sclerosis and the major histocompatibility complex (MHC). - Burrell, A; Handel, A; Ramagopalan, S; Ebers, G; Morahan, J (2011)
Multiple sclerosis (MS) is a complex disorder of the central nervous system characterized by demyelination, axonal loss, and inflammation. The cause of MS is currently unknown although genetic and environmental factors contribute to etiology. The relative importance of each has been disputed; however, now it is clear that much of the disease results from the interaction of the environment and the genetics. Epigenetic modifications within the major histocompatibility complex (MHC) likely mediate interactions at this locus with current known environmental risk factors--vitamin D, Epstein-Barr virus, and smoking. Maternal parent-of-origin effects, month of birth effects and transgenerational differences in allele frequency are also evident in MS and may be mediated by sex-specific epigenetic mechanisms. Differences in epigenetic marks characterize monozygotic twin pairs and may explain discordance. There is promise of potential therapeutic strategies to be found in the epigenetic mechanisms at work in MS.